2021
DOI: 10.2217/nnm-2021-0080
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic Acid Nanoparticle-Encapsulated MicroRNA-125B Repolarizes Tumor-Associated Macrophages in Pancreatic Cancer

Abstract: Aim: To investigate a novel strategy to target tumor-associated macrophages and reprogram them to an antitumor phenotype in pancreatic adenocarcinoma (PDAC). Methods: M2 peptides were conjugated to HA-PEG/HA-PEI polymer to form self-assembled nanoparticles with miR-125b. The efficacy of HA-PEI/PEG-M2peptide nanoparticles in pancreatic tumors from LSL-KrasG12D/+, LSL-Trp53R172H/+, Pdx1-Cre genetically engineered mice was evaluated. Results: In vitro M2 macrophage-specific delivery of targeted nanoformulations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 25 publications
(35 reference statements)
0
19
0
Order By: Relevance
“…The treatments produced a potent antitumor immune memory that prevented tumor reformation after a secondary challenge, providing a potential strategy for preventing tumor recurrence. Injection of microRNA-125b encapsulated in a hyaluronic acid nanoparticle reprogrammed tumor-associated macrophages from protumor to antitumor phenotypes 236 …”
Section: Late Diagnosismentioning
confidence: 99%
“…The treatments produced a potent antitumor immune memory that prevented tumor reformation after a secondary challenge, providing a potential strategy for preventing tumor recurrence. Injection of microRNA-125b encapsulated in a hyaluronic acid nanoparticle reprogrammed tumor-associated macrophages from protumor to antitumor phenotypes 236 …”
Section: Late Diagnosismentioning
confidence: 99%
“…Hyaluronic acid nanoparticle-encapsulated miRNA-125b reprogrammed TAMs to an antitumor phenotype in PDAC[ 143 ]. M2-TAM-targeting nanomicelles were created to simultaneously deliver PI3K-γ inhibitor NVP-BEZ 235 and CSF-1R-siRNA, leading to specific TAM reprogramming and antitumor immune response activation[ 144 ].…”
Section: Tams and Targeted Therapies Of Digestive System Malignant Tu...mentioning
confidence: 99%
“…The final results showed that this dual delivery system polarized inhibitory TAM, recruited CTLs, and down-regulated Treg, thus eliciting a potent antitumor immune response. In another study, Parayath et al constructed M2 peptide-modified polymer NPs for TAM-targeted miR-125b delivery [ 112 ]. The results showed that intraperitoneal administration of M2-targeted NPs showed preferential accumulation at the tumor site, and the ratio of M1-to-M2-TAM increased more than fourfold.…”
Section: Well-designed Nanosystems For Different Pdac Therapeuticsmentioning
confidence: 99%